Chemical compounds contained in young and mature leaves of agarwood species Wikstroemia tenuiramis and its antioxidant properties (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Batubara R, Hanum TI, Affandi O, Wahyuni HS. 2020. Chemical compounds contained in young and mature leaves of agarwood species Wikstroemia tenuiramis and its antioxidant properties. Biodiversitas 21: 4616-4622. The genus Wikstroemia is one of the genus of agarwood producing trees which has not been widely researched and published. One type of this genus is Wikstroemia tenuiramis Miq, which grows naturally in North Sumatra, the leaves are like other types of agarwood leaves can be used as raw material for agarwood leaves tea. A research has been conducted to determine the chemical contents contained in the young and mature leaves of agarwood plants species W. Tenuiramis. This research methods applied qualitative analysis using phytochemical screening, quantitative analysis to determine tannin content using titration method, antioxidant activity analysis using 2,2-diphenil-1-picrylhydrazil (DPPH) method, and compound tracing using Py-gas chromatography-mass spectrometry (Py-GC-MS) instruments. The qualitative phytochemical analysis results showed no difference in chemical compounds contained in both the young and mature leaves. Both the young and mature leaves contained flavonoids, triterpenoids, and tannins, and did not contain alkaloids, steroids and saponins. The young contained tannins of 1.079 ± 0.001% and the mature contained tannins of 4.645 ± 0.021%, not significant statistically. Py-GC-MS analysis showed the presence of various 30 bioactive compounds contained in both young and mature leaves. The analysis results also showed that both the young and mature leaves had very strong antioxidant activity. Our findings suggest that the two types of leaves have equal utility value of in term of chemical contents and antioxidant potentials.
Keywords: Agarwood, antioxidants, mature leaves, phytochemicals, py-GC-MS, young leaves, Wikstroemia tenuiramis